The Impact of Gene Therapy on the Treatment of Hypertrophic Cardiomyopathy – A Literature Review - Lesiczka-Fedoryj, Katarzyna; Walczak, Anna; Ciraolo, Silvia; Kościuszko, Zuzanna; Kurza, Katarzyna; Czerwonka, Matylda; Podolec, Julianna; Kulczycka–Rowicka, Agnieszka; Wojda, Joanna; Sobiński, Adam (Quality in Sport, 2025)
Introduction: Hypertrophic cardiomyopathy (HCM) is the most common genetic cardiovascular disorder. HCM is defined by increased left ventricular (LV) wall thickness or mass not attributable solely to abnormal loading conditions. It is chronic, heterogeneous in terms of its clinical presentation, ranging from absence of symptoms in fenotype to severe left ventricular hypertrophy, sudden cardiac death and end-stage heart failure at young age. Aim of the Study: This study aims to explore the potential of gene therapy as a novel therapeutic approach for HCM, including the advancements, ongoing clinical trials, and associated challenges. Materials and methods: More than 55 articles were analysed. They were found using the PubMed search engine focusing on studies investigating gene therapy techniques, including gene replacement, allele-specific silencing, and genome editing with CRISPR/Cas9. Results: Gene therapy has shown promising results in preclinical models. Early clinical studies are currently underway, aiming to assess the safety and efficacy of gene therapy on humans. Additionally, techniques such as allele-specific silencing and CRISPR-Cas9 present new opportunities in gene therapy. Despite the successes observed in preclinical research, it is crucial to evaluate the safety profile on humans and to address challenges such as off-target effects and the immune response to the introduced molecules. Conclusions: Gene therapy is emerging as a promising innovation in the treatment of HCM, enabling targeted correction of the genetic causes of the disease. Despite recent advancements, further long-term studies are still necessary to confirm its safety, efficacy, and potential for broad application before it can become a standard therapeutic option.